2017
DOI: 10.3892/ijo.2017.3874
|View full text |Cite
|
Sign up to set email alerts
|

Müllerian inhibiting substance inhibits an ovarian cancer cell line via β-catenin interacting protein deregulation of the Wnt signal pathway

Abstract: Müllerian inhibiting substance/anti-Müllerian hormone (MIS/AMH) has been suggested as a biotherapeutic agent in gynecological cancers that highly express the MIS/AMH type II receptors (MISRII/AMHRII) but the anticancer mechanisms by which MIS/AMH acts are not fully understood. Our experiments show that MIS/AMH inhibits ovarian cancer by deregulating the Wnt signal pathway via the β-catenin interacting protein (ICAT). MIS/AMH inhibition of ICAT by small interfering RNAs (siRNA) decreased ICAT driven ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…We believe that the slight pro‐rAMH activity is due to the presence of a small amount (up to 5%) of half‐cleaved rAMH in the preparation. Note that the biological activity of purified C ‐rAMH was comparable with that of the heterogeneous preparation of full‐length rAMH previously obtained in a more complicated way in other studies (Lorenzo et al, ; Park et al, ). Our results indicate the feasibility of C ‐rAMH‐based antitumor drugs development.…”
Section: Resultssupporting
confidence: 81%
“…We believe that the slight pro‐rAMH activity is due to the presence of a small amount (up to 5%) of half‐cleaved rAMH in the preparation. Note that the biological activity of purified C ‐rAMH was comparable with that of the heterogeneous preparation of full‐length rAMH previously obtained in a more complicated way in other studies (Lorenzo et al, ; Park et al, ). Our results indicate the feasibility of C ‐rAMH‐based antitumor drugs development.…”
Section: Resultssupporting
confidence: 81%
“…The same product, purchased from alternative companies, will be used in future studies. Finally, the working concentration of rhAMH was diluted to 10 µg/ml according to previous experiments (30,31). It would have been ideal to instead perform a dose-response analysis to identify the optimal working concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Since most gynecologic tumors originate from Müllerian duct derived tissues and MIS/AMH causes regression of the Müllerian duct, it is expected to inhibit the growth of the gynecologic tumors via MIS/AMH receptor-mediated mechanism [ 3 11 ]. Furthermore, several lines of evidence suggest that MIS/AMH inhibits proliferation in tissues and cell lines of MIS/AMH receptor-expressing gynecologic malignancies such as ovarian cancer [ 12 13 14 15 16 17 ], cervical cancer [ 18 19 20 21 ], and endometrial cancer [ 22 23 ]. In vitro studies using human epithelial ovarian cancer cell line (OVCAR 8) revealed that MIS/AMH inhibits growth of epithelial ovarian cancer cells [ 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIS/AMH not only plays an important role in fetal sexual development, but also inhibits growth of tumors originating from the Müllerian duct where the MIS/AMH receptor is expressed [ 9 10 11 ], such as ovarian [ 12 13 14 15 16 17 ], cervical [ 18 19 20 21 ], and endometrial cancers [ 22 23 ]. Masiakos et al [ 14 ] reported that MIS/anti-Müllerian hormone type II receptor (AMHRII) is expressed at a high frequency in cells detected in ascites of patients with stage III/IV ovarian cancer, and MIS/AMH cause the growth inhibition of ovarian cancer cells expressing the MIS/AMH receptor.…”
Section: Introductionmentioning
confidence: 99%